Pencucian Citra SDM Warisan Kolonial, Peletakan Paradigma SDM Baru: Mungkinkah? - Taufiq Ismail (Millah: Journal of Religious Studies, 2005)
This article tries to present a new paradigm of human resources, instead of maintaining the old one which is part of colonial heritage. This old paradigm pays more attention or respect to status, rights, and one who is in power. More over this paradigm disregards the importance of education, by giving little attention on it especially in matter of fund. By eliminating many of these outdated ideas, the Indonesians have to work hard to create the new one by respecting the local genius ideas, best tradition, religion and creating the new paradigm which pays respect to the process education instead of the result only. The new paradigm pays more attention to poor, and the needy ones, the duties of the leaden, and providing enough fund to the education.